Floral microcharacters in Lessingianthus (Vernonieae, Asteraceae) and their taxonomic implications - Angulo, Maria Betiana (2014)
Micromorphological characters of 113 species of the South American genus Lessingianthus H.Rob.(Vernonieae, Asteraceae) were analyzed to evaluate their reliability as taxonomic markers. The corolla pubescence was studied in detail for the first time in the genus. Glandular and non-glandular trichomes were studied and described. The trichome types allow differentiation among related species, but do not reflect the relationships among species groups. On the other hand, the basal stylar node only occurs in a distinctive group of species within the genus. The apical appendage of the anthers is non-glandular in all species of the genus. Several character states analyzed in Lessingianthus are often widespread in other related genera of Vernonieae. Therefore, Lessingianthus can be circumscribed only by a combination of micro- and macromorphological features.